Strategic Planning and Innovation as Essential Determinants of MSMEs' International Performance : Evidence from Emerging Markets - Junaidi Junaidi; Sudarmiatin Sudarmiatin (Universitas 45 Surabaya, 2025)
The internationalisation of MSMEs in emerging markets faces complex challenges, yet understanding of the critical factors that influence their international performance is limited. This study aims to analyse the role of strategic planning and innovation as critical success factors in the international performance of MSMEs in emerging markets. Using a quantitative approach, a survey was conducted on 600 creative industry MSMEs in Indonesia, with data analysis using Structural Equation Modeling (AMOS). Results show that strategic planning and innovation have a significant positive influence on the international performance of MSMEs, with innovation acting as a key mediator. Management capability, market orientation and international business networks are identified as additional critical success factors. Market dynamics moderate the relationship between innovation and international performance, while the effectiveness of strategic planning varies by MSME size. The findings contribute to the development of an integrated model of MSME internationalisation and highlight the importance of a holistic approach in supporting MSME global expansion. Implications include recommendations for the development of integrated training programmes and policies that encourage innovation and facilitate access to international networks for MSMEs.